MINAT MENULIS PUISI PADA SISWA KELAS VIII DI SMP NOMMENSEN JAMBI - Situmeang, Hizkia Mustika Ida; Nazurty; Rachmad Pratama, Deri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interest in writing poetry among junior high school students remains a significant issue in Indonesian language learning, including at Nommensen Middle School in Jambi. Low interest in writing poetry is seen as a significant issue because it is a creative literacy skill that plays a role in Indonesian language learning. This study aims analyze the factors causing low interest in writing poetry among eighth-grade students at Nommensen Middle School in Jambi. This study used a descriptive qualitative research method with a single case study approach. The research subjects consisted of eighth-grade students and Indonesian language teachers at Nommensen Middle School in Jambi. Data were obtained through observation, structured interviews, and documentation. The results showed that students' interest in writing poetry was low, as evidenced by their passive attitudes during the learning process, lack of interest in poetry writing assignments, and minimal effort by students to understand the elements of poetry. Internal factors influencing low interest include lack of self-confidence, limited vocabulary, and a weak understanding of the elements of poetry. External factors include teachers' predominantly lecture-based learning methods, underutilization of learning media, and peer influence that distracts students from focusing. This study concludes that low interest in writing poetry is the result of an interaction between internal factors and the learning environment.